140k views
1 vote
2. Using the substitution method Zoe is solving the following system of

equations algebraically:
y + 5x = -2
4x - 7y=-14
Which equivalent equation could Zoe use?
(1) 4(-5x - 2) + 5x =-14
(3) 4x - 7(- 5x – 2)=-14
(2) 4(5x – 2) + 5x =-14
(4) 4x – 7(5x – 2)=-21

User Rckehoe
by
5.7k points

1 Answer

4 votes
1. You want to get one variable by itself, in this case Y in the first one is easier. You would get y = -5x -2, so you substitute that in for Y in the second equation
User Exos
by
5.0k points